Ketimpangan Ekologis Global dalam Produksi Ketidakamanan Lingkungan - Keysha Natania Putri Muntu; Imam Fadhil Nugraha (Lampung Center for Global Studies (LCGS), 2026)
This research discusses the phenomenon of fast beauty as part of the development global capitalism, which remains underexplored within Internatial Relation studies. Unlike previous research that focuses on individual consumer risks or corporate sustainability, this study shifts the analytical focus toward ecological risks at the global level. By comparing the logic of fast beauty and fast fashion within a global political economy perspective, this study argues that fast beauty is not only about consumer behaviour, or digital marketing, but reflects a broader pattern of structured consumerism. Through complex global supply chains, ranging from resource extraction in the global south to distribution in global north consumer market. This study shows that rapid production cycles, high output volume, and trend influencer-driven business model intensify ecological pressures, while environmental costs are not distributed evenly within the production system. As a result, ecological burdens are disproportionately shifted to production regions with greater vulnerability.